21-Hydroxypregnane 21-O-malonylation, a crucial step in cardenolide biosynthesis, can be achieved by substrate-promiscuous BAHD-type phenolic glucoside malonyltransferases from Arabidopsis thaliana and homolog proteins from Digitalis lanata - Tropper, Marina; Höhn, Stephanie; Wolf, Laura-Sophie; Fritsch, Julia; Kastner-Detter, Nina; Rieck, Christoph; Munkert, Jennifer; Meitinger, Nadine; Lanig, Harald; Kreis, Wolfgang (Phytochemistry, 2021)
Three putative 21-hydroxypregnane 21-O-malonyltransferases (21MaT) from Digitalis lanata were partially purified.Two of them were supposed to be BAHD-type enzymes. We were unable to purify them in quantities necessary for reliable sequencing. We identified two genes in A. thaliana coding for substrate-promiscuous BAHDtype phenolic glucoside malonyltransferases (AtPMaT1, AtPMaT2) and docked various 21-hydroxypregnanes into the substrate-binding site of a homology model built on the BAHD template 2XR7 (NtMaT1 from N. tabacum). Recombinant forms of Atpmat1 and Atpmat2 were expressed in E. coli and the recombinant enzymes characterized with regard to their substrate preferences. They were shown to malonylate various 21-hydroxypregnanes. The Atpmat1 sequence was used to identify candidate genes in Digitalis lanata (Dlmat1 to Dlmat4). Dlmat1 and Dlmat2 were also expressed in E. coli and shown to possess 21-hydroxypregnane 21-O-malonyltransferase activity.<br
Keywords: Digitalis lanata; Plantaginaceae; Foxglove; Protein purification; Protein modeling; Gene expression analysis; Cardenolides; BAHD; Pregnane 21-O-malonyltransferase

In silico, in vitro, and structural investigations on BAHD-enzymes from different species able to malonylate 21-hydroxypregnanes - Tropper, Marina; Wolf, Laura-Sophie; Lanig, Harald; Kreis, Wolfgang (PLANTA MEDICA, 2021)
CRIS-Team WoS Importer:2021-12-31

RNAi-mediated gene knockdown of progesterone 5β-reductases in Digitalis lanata reduces 5β-cardenolide content - Klein, Jan; Horn, Elisa; Ernst, Mona; Leykauf, Tim; Leupold, Tamara; Dorfner, Maja; Wolf, Laura-Sophie; Ignatova, Anastasiia; Kreis, Wolfgang; Munkert, Jennifer (Plant Cell Reports, 2021)
Key message: Studying RNAi-mediated DlP5βR1 and DlP5βR2 knockdown shoot culture lines of Digitalis lanata, we here provide direct evidence for the participation of PRISEs (progesterone 5β-reductase/iridoid synthase-like enzymes) in 5β-cardenolide formation. Abstract: Progesterone 5β-reductases (P5βR) are assumed to catalyze the reduction of progesterone to 5β-pregnane-3,20-dione, which is a crucial step in the biosynthesis of the 5β-cardenolides. P5βRs are encoded by VEP1-like genes occurring ubiquitously in embryophytes. P5βRs are substrate-promiscuous enone-1,4-reductases recently termed PRISEs (progesterone 5β-reductase/iridoid synthase-like enzymes). Two PRISE genes, termed DlP5βR1 (AY585867.1) and DlP5βR2 (HM210089.1) were isolated from Digitalis lanata. To give experimental evidence for the participation of PRISEs in 5β-cardenolide formation, we here established several RNAi-mediated DlP5βR1 and DlP5βR2 knockdown shoot culture lines of D. lanata. Cardenolide contents were lower in D. lanata P5βR-RNAi lines than in wild-type shoots. We considered that the gene knockdowns may have had pleiotropic effects such as an increase in glutathione (GSH) which is known to inhibit cardenolide formation. GSH levels and expression of glutathione reductase (GR) were measured. Both were higher in the Dl P5βR-RNAi lines than in the wild-type shoots. Cardenolide biosynthesis was restored by buthionine sulfoximine (BSO) treatment in Dl P5βR2-RNAi lines but not in Dl P5βR1-RNAi lines. Since progesterone is a precursor of cardenolides but can also act as a reactive electrophile species (RES), we here discriminated between these by comparing the effects of progesterone and methyl vinyl ketone, a small RES but not a precursor of cardenolides. To the best of our knowledge, we here demonstrated for the first time that P5βR1 is involved in cardenolide formation. We also provide further evidence that PRISEs are also important for plants dealing with stress by detoxifying reactive electrophile species (RES).
CRIS-Team Scopus Importer:2021-07-02
Keywords: Cardenolide biosynthesis; Digitalis lanata; Glutathione; Progesterone 5β-reductases (P5βR); Reactive electrophile species; RNAi-mediated knockdown